GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 29699 species occurrences available in GBIF matching the query: TaxonKey: Charadrius wilsonia Ord, 1814. The dataset includes 29699 records from 96 constituent datasets: 123 records from KUBI Ornithology Collection. 8 records from DMNS Egg Collection (Arctos). 41 records from Colección nacional de zoología. 10 records from NCSM Birds Collection. 1 records from Database Schema for UC Davis Wildlife museum. 29 records from DMNS Bird Collection (Arctos). 91 records from NatureServe Network Species Occurrence Data. 1 records from Caracterización de la avifauna de las cuencas de los Ríos Cañas (Dibulla–Guajira), Garupal (Valledupar–Cesar), Arroyo Grande (San Juan de Nepomuceno–Bolívar), Aipe (Huila), Yaví (Tolima), Dagua (Valle del Cauca) como insumo para la identificación de oportunidades de conservación y de recuperación de servicios ecosistémicos del bosque seco.. 8 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 62 records from iNaturalist research-grade observations. 8 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 54 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 102 records from Great Backyard Bird Count. 7 records from PSM Vertebrates Collection. 2 records from NBM birds. 224 records from Riqueza específica, distribución y abundancia de aves acuáticas en la ensenada de La Paz, Baja California Sur, México. 82 records from Bird specimens. 254 records from WFVZ Bird Collections. 7 records from Riqueza específica, distribución y abundancia de aves terrestres y marinas en Isla San José, Golfo de California, Baja California Sur, México. 9 records from Perot Museum of Nature and Science. 8 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 8 records from Collection Aves (spirit preserved) SMF. 6 records from CHAS Vertebrates. 53 records from Macaulay Library Audio and Video Collection. 1 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM (Aves). 71 records from CM Birds Collection. 13 records from SBMNH Vertebrate Zoology. 6 records from UNSM Vertebrate Specimens. 11 records from Ohio State University Tetrapod Division - Bird Collection (OSUM). 6 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 9 records from Ornithology Collection. 178 records from UMMZ Birds Collection. 12 records from Avifauna de la laguna Madre de Tamaulipas. 1 records from Colección de Ornitología - Museo de Ciencias Naturales de La Salle. 25 records from CUMV Bird Collection (Arctos). 1 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 14 records from UWBM Ornithology Collection. 10 records from Bird Specimens in the Museum of Nature and Human Activities, Hyogo, Japan. 4 records from HSU Wildlife Eggs and Nests. 3 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 24 records from MMNH Museum Bird Collection. 32 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Aves. 20 records from DMNH Birds. 5 records from Canadian Museum of Nature Bird Collection. 2 records from SysTax - Zoological Collections. 2 records from Birds collection of Yamashina Institute for Ornithology. 29 records from UCLA Donald R. Dickey Bird and Mammal Collection. 2 records from Bird Collection of Museum and Institute of Zoology PAS. 3 records from Censo del Zarapito Trinador (Numenius phaeopus) y Otras Aves Acuáticas en el Parque Nacional Natural Sanquianga. 1 records from Geographically tagged INSDC sequences. 52 records from ORN. 6 records from KUBI Ornithology Tissue Collection. 3 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 2 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 19 records from Colección Ornitológica de la Universidad del Valle. 262 records from Aves Acuáticas en el Caribe Colombiano Entre 2007 y 2009. 10 records from Cowan Tetrapod Collection - Birds. 11 records from NYSM Birds. 2 records from UCM Bird Collection (Arctos). 5 records from Base de datos de aves mexicanas del Natural History Museum, Tring, Inglaterra. 8 records from Collection Aves (bird skins) SMF. 1 records from Bird Collection. 10 records from MVZ Egg and Nest Collection (Arctos). 1 records from Eggs Specimen. 28 records from CNAV/Coleccion Nacional de Aves. 25981 records from EOD - eBird Observation Dataset. 9 records from naturgucker. 149 records from Aves Marinas y Playeras en el PNN Sanquianga y la Bocana de Iscuandé entre 2007 y 2009. 319 records from NMNH occurrence DwC-A. 49 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 29 records from El Censo Neotropical de Aves Acuáticas en Colombia (CNAA): 2002 - 2011. 12 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 14 records from Natural History Museum (London) Collection Specimens. 5 records from UMZC Zoological Specimens. 45 records from MVZ Bird Collection (Arctos). 16 records from CAS Ornithology (ORN). 7 records from RBINS collections. 22 records from MLZ Bird Collection (Arctos). 3 records from Australian National Wildlife Collection provider for OZCAM. 182 records from Museum of Comparative Zoology, Harvard University. 2 records from CRCM Vertebrate Collection. 2 records from Vertebrates of the Gothenburg Natural History Museum (GNM). 8 records from LACM Vertebrate Collection. 180 records from AMNH Bird Collection. 33 records from SDNHM Birds Collection. 28 records from Colección de Tejidos del Instituto Alexander Von Humboldt. 203 records from DATAVES. 1 records from MZFC/Coleccion de Aves. 1 records from Queensland Museum provider for OZCAM. 9 records from MSB Bird Collection (Arctos). 7 records from TTRS Ornithology. 2 records from Birds Specimens. 4 records from Lund Museum of Zoology (MZLU). 40 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 1 records from Aves MZS. 233 records from Field Museum of Natural History (Zoology) Bird Collection.
Keywords: GBIF; biodiversity; species occurrences